Characterization of forest fragments occupied by the critically endangered and endemic San Martín titi monkey (Plecturocebus oenanthe) - Rubio Vargas, Carina Linda; Cerón Cancharis, Zoila Lasmit; Heymann, Eckhard W. (Frontiers in Conservation Science, 2024)
This study describes the characteristics of forest fragments occupied by a Critically Endangered endemic Peruvian primate, the San Martín titi monkey, Plecturocebus oenanthe (Pitheciidae; Platyrrhini). We selected 45 fragments; 20 had already been surveyed in 2015 by the Proyecto Mono Tocón (six of these had been further split, resulting in 27 fragments); additional 18 fragments were randomly selected from satellite images. We surveyed these fragments for the presence of P. oenanthe and determined characteristics of the fragments (size, shape, tree density, canopy height) and of the landscape (distance to nearest fragment and road). We also examined changes in the number of fragments and in forest cover between 2015 and 2019. We encountered P. oenanthe in all surveyed fragments except for the smallest on (0.2 ha). Our findings suggest that P. oenanthe can persist in fragments with a wide range of characteristics, particularly with regard to size and tree density. Unless fragmentation continues and overall forest cover in the area diminishes further, the species may be able to persist even in a fragmented landscape, provided that the matrix allows for movements between fragments. However, persistence might not be over the long-term if groups are not reproductive, populations become too small, and reduced gene flow results in inbreeding.